Pteridófitas do final do cretáceo da Ilha Livingston (Península Antártica) e Cerro Guido (Patagônia Chilena) e suas implicações evolutivas, paleoambientais, paleogeográficas - Trevisan, Cristine (Universidade do Vale do Rio dos Sinos, 2018)
The knowledge of fossil plants lived in the Antarctic Peninsula and Patagonia until the arrival of colder climates at the end of the Eocene (Reguero et al., 2013), allows us to assess the biodiversity of past forests in high latitudes, help in understanding their modern distribution and about the processes adopted in its dispersion, as a response to changes in climate and paleogeography. In these paleoflora, pteridophytes are an important element and have shown an easy adaptation to different types of soils and unstable conditions due to nearby tectonic processes.
Keywords: Thyrsopteris; Pteridófita; Fósseis; Paleontologia-cretáceo; Cyatheales; Península Antártica; Ilha Livingston; Hannah Point; Pteridophyte; Fossils; Cretaceous paleontology; Cyathales; Antarctic Peninsula; Livingston Island; ACCNPQ::Ciências Exatas e da Terra::Geologia